The prepositional passive in Lexical Functional Grammar - Findlay, J (CSLI Publications, 2016)
The aim of this paper is to provide an adequate analysis in LFG of the prepositional passive, e.g. 'That problem has been dealt with', 'My pen has been written with'. This construction has been examined in LFG before by Bresnan (1982), Lødrup (1991), and Alsina (2009), but empirical and theoretical problems, some well-documented, some new, mean that such proposals cannot be maintained. Instead, I offer an account couched in recent work on the mapping between grammatical functions and arguments (Asudeh et al., 2014; Findlay, 2014a) that treats the defining characteristic of the prepositional passive not as purely syntactic, but rather as being located at the interface between syntax and semantics.